Nonsteroidal anti-inflammatory therapy: changes on renal function of healthy dogs - Borges, Marina; Marini Filho, Rivaldo; Laposy, Cecília Braga; Guimarães-Okamoto, Priscylla Tatiana Chalfun [UNESP]; Chaves, Marina Platzeck; Vieira, André Nanny Le Sueur; Melchert, Alessandra [UNESP] (Sociedade Brasileira para o Desenvolvimento da Pesquisa em Cirurgia, 2013)
PURPOSE: To evaluate the renal function in healthy dogs submitted to nonselective and preferential COX-2 nonsteroidal anti-inflammatory drug (NSAID) therapy. METHODS: Twenty four healthy dogs were distributed into four groups (G) (n=6): ketoprofenG - treated with ketoprofen; nimesulideG - treated with nimesulid; meloxicanG - treated with meloxican; and etodolacG - treated with etodolaco. All the dogs received the NSAIDs for 10 days by oral route. Physical examination and renal function (urinalysis, urinary sodium and gamma-glutamyl transpeptidase (GGT), serum urea, creatinine, potassium and sodium, and endogenous creatinine clearance) were evaluated before, after five and ten days (T0, T5 and T10) of the treatment in all groups. RESULTS: Changes were observed in urinalysis, with a significant increase in renal cells in the urine at T5 and T10 in nimesulideG. Significant reduction in urinary sodium in nimesulideG at T5 was observed. The clearance values were lower in ketoprofenG at T10. CONCLUSIONS: Meloxicam and etodolac were the drugs that have proven to be safer for short-term therapy in healthy dogs in relation to renal function. NSAIDs ketoprofen and nimesulide should be used judiciously in dogs with renal dysfunction, since there are promoted changes in renal function.
Keywords: Anti-Inflammatory Agents, Non-Steroidal; Drug Effects; Kidney; Dogs